Monitoring aging‐associated structural alterations in Caenorhabditis elegans striated muscles via polarization‐dependent second‐harmonic generation measurements. Issue 12 (26th August 2021) - Tsafas, Vassilis; Giouroukou, Konstantina; Kounakis, Konstantinos; Mari, Meropi; Fotakis, Costas; Tavernarakis, Nektarios; Filippidis, George
Abstract: The in‐vivo elucidation of the molecular mechanisms underlying muscles dysfunction due to aging via non‐invasive label free imaging techniques is an important issue with high biological significance. In this study, polarization‐dependent second‐harmonic generation (PSHG) was used to evaluate structural alterations in the striated muscles during Caenorhabditis elegans lifespan. Young and old wild‐type animals were irradiated. The obtained results showed that it was not feasible to detect differences in the structure of myosin that could be correlated with the aging of the worms, via the implementation of the classical, widely used, cylindrical symmetry model and the calculation of the SHG anisotropy values. A trigonal symmetry model improved the extracted results; however, the best outcome was originated from the application of a general model. Myosin structural modifications were monitored via the estimation of the difference in spectral phases derived from discrete Fourier transform analysis. Age classification of the nematodes was achieved by employing both models, proving the usefulness of the usage of PSHG microscopy as a potential diagnostic tool for the investigation of muscle diseases. Abstract : The employment of label free, non‐destructive imaging techniques as novel diagnostic tools for the in‐vivo monitoring of muscular changes due to aging is an important issue with high biological significance. Polarization‐dependent second‐harmonic generation measurements were used for age classification of the Caenorhabditis elegans samples and evaluation of structural alterations in their striated muscles during the worm lifespan. The obtained results indicate the usefulness of this technique as a potential new diagnostic tool for the investigation of muscle disorders.